Implementasi Program Escete Dalam Transformasi Pelayanan Keuangan Ksp Credit Union Bahtera Sejahtera Ditinjau Dari Teori Instituisional - Nona Serly, Veronika; Pati Sanga, Konstantinus; Lamawitak, Paulus Libu (Universitas Nusa Nipa Maumere, 2026)
The development of digital technology in recent years has had a significant impact on almost all sectors, especially the financial sector. Digitalization is no longer an option but a fundamental necessity for financial institutions, including Savings and Loan Cooperatives (KSP), to remain competitive and capable of providing efficient, accurate, and high-quality services. The need for technology that can improve service processes, data management, and transactions has become increasingly urgent amid the growing complexity of cooperative members’ demands and the increasing competition among financial institutions.This study aims to analyze the transformation of financial services at KSP Credit Union Bahtera Sejahtera through the implementation of the Escete Program, an online-based digital system. Before 2019, this cooperative used the SIKOPDIT CS system which operated offline, resulting in difficulties in data synchronization and service efficiency. The method used in this study is a qualitative descriptive approach using the perspective of Institutional Theory to examine the motivations behind organizational change.The results of the study indicate that the transition from SIKOPDIT CS to the Escete Program is not merely a technical change but also a form of organizational adaptation to three institutional pressures: (1) Coercive Pressure arising from regulations requiring financial transparency; (2) Mimetic Pressure as an effort to emulate the success of banking digitalization; and (3) Normative Pressure to meet members’ expectations and the professionalism of human resources. The implementation of the Escete Program has proven to improve real-time data accuracy, accelerate services through Android integration, and transform the organizational work culture into a more modern and transparent one.